Tlingit wood carver known as Yucast in his studio, Alaska, 1898 - Pillsbury, Arthur C. (Arthur Clarence)
Older man in shirtsleeves sits in woodcarving studio, holding a knife in one hand and an partially carved staff; in background other carved and painted items can be seen. Copy print made from original at Seattle Public Library